2018
DOI: 10.1021/acs.jctc.8b00081
|View full text |Cite
|
Sign up to set email alerts
|

Relative Ligand-Binding Free Energies Calculated from Multiple Short QM/MM MD Simulations

Abstract: We have devised a new efficient approach to compute combined quantum mechanical (QM) and molecular mechanical (MM, i.e. QM/MM) ligand-binding relative free energies. Our method employs the reference-potential approach with free-energy perturbation both at the MM level (between the two ligands) and from MM to QM/MM (for each ligand). To ensure that converged results are obtained for the MM → QM/MM perturbations, explicit QM/MM molecular dynamics (MD) simulations are performed with two intermediate mixed states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…This gave even better results with a precision of 0.5-0.9 kJ/mol, a MAD of 4.7 ± 0.2 and a R 2 correlation of 0.86 ± 0.04. Recently, we have shown that similar results can be obtained with approximately a fourth of the computational effort using multiple short QM/MM simulations [23] or by using non-equilibrium simulations and Jarzynski's equality [32][33][34].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…This gave even better results with a precision of 0.5-0.9 kJ/mol, a MAD of 4.7 ± 0.2 and a R 2 correlation of 0.86 ± 0.04. Recently, we have shown that similar results can be obtained with approximately a fourth of the computational effort using multiple short QM/MM simulations [23] or by using non-equilibrium simulations and Jarzynski's equality [32][33][34].…”
Section: Introductionsupporting
confidence: 58%
“…Relative QM/MM binding affinities between two ligands, L 0 and L 1 , were estimated by the reference-potential method with QM/MM sampling (RPQS) [22,23]. In this approach, the ∆∆G bind free energies, calculated at the MM level, as described in the previous section, are corrected by a FEP calculation for each ligand in the method space, from the MM potential to the QM/MM potential, as is shown by the thermodynamic cycle in Fig.…”
Section: Qm/mm Fep Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While electronic structure calculations are now possible on quite large systems using low‐scaling methods and efficient codes, QM/MM methods offer a combination of flexibility and speed that makes them attractive and practical. QM/MM methods allow calculation of electronic properties of (a small region in) biomolecular systems and are finding application in many areas of biomolecular science (e.g., in the calculation of spectroscopic properties, photochemistry, p K a s, and predictions of ligand‐binding affinities) and beyond (e.g., chemistry of solid‐state materials), but is particularly popular for the study of reactions (and interactions) in enzymes . A QM/MM method was first applied to an enzyme‐catalyzed reaction by Warshel and Levitt in their seminal study of the reaction mechanism of hen egg white lysozyme .…”
Section: Qm/mm Modeling Of Enzyme Reactionsmentioning
confidence: 99%